2017
DOI: 10.1002/cctc.201700986
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Reduction of Phosphine Oxides, Sulfoxides, and N‐Oxides with Hydrosilanes using a Borinic Acid Precatalyst

Abstract: The general reduction of phosphine oxides, sulfoxides, and amine N‐oxides was achieved by combining bis(2‐chlorophenyl)borinic acid with phenylsilane. The reaction was shown to tolerate a wide range of substrates and could be performed under mild conditions, with only 2.5 mol % of the easily synthesized catalyst. Mechanistic investigations pointed to a key borohydride as the real catalyst and at bis(2‐chlorophenyl)borinic acid as a precatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Borinic acids were employed by Blanchet and co-workers with silane reductants for the metal-free reduction of phosphine oxides, sulfoxides, and amine N -oxides (Scheme ). Analysis of the mechanism indicated that the active catalyst was a borohydride derived from the borinic acid and the silane. Finally, simple boric acid has been used to promote the reduction of quinolines using Hantzsch esters through coordination of the quinoline nitrogen to the boron …”
Section: Other Reactivitymentioning
confidence: 99%
“…Borinic acids were employed by Blanchet and co-workers with silane reductants for the metal-free reduction of phosphine oxides, sulfoxides, and amine N -oxides (Scheme ). Analysis of the mechanism indicated that the active catalyst was a borohydride derived from the borinic acid and the silane. Finally, simple boric acid has been used to promote the reduction of quinolines using Hantzsch esters through coordination of the quinoline nitrogen to the boron …”
Section: Other Reactivitymentioning
confidence: 99%
“…For examples, Cu­(OTf) 2 , CeCl 3 , B­(C 6 F 5 ) 3 , electrophilic fluorophosphonium, bis­(pertrifluoromethylcatecholato)­silane, and trityl cations were used as Lewis acid catalysts. Brønsted acids, e.g., diarylphosphoric acid, CF 3 SO 3 H, and borinic acid, were also employed in catalytic deoxygenation of phosphine oxides at elevated temperatures. The recently reported electrochemical reduction of phosphine oxides can also be considered for Lewis acid activation with borate or aluminum cations. , …”
Section: Introductionmentioning
confidence: 99%
“…More recently Oestreich, Stephan and co‐workers developed a reduction catalyzed by B(C 6 F 5 ) 3 or electrophilic fluorophosphonium cations 1 a‐b , [20] which proved compatible with a broad range of functional groups (Figure 1). Brønsted acids such as phosphoric acids 2 , [21] and TfOH, [22] or borinic acids 3 [23] have recently been introduced as mild catalysts for this reduction. In this context, we report herein a new simple and mild procedure to reduce phosphine oxides into phosphines using a silane as a reducer and a trityl cation as an initiator.…”
Section: Introductionmentioning
confidence: 99%